Generation of a flood susceptibility map of evenly weighted conditioning factors for Hungary - Sarkadi, Noémi; Pirkhoffer, Ervin; Lóczy, Dénes; Balatonyi, László; Geresdi, István; Fábián, Szabolcs Ákos; Varga, Gábor; Balogh, Richárd; Gradwohl-Valkay, Alexandra; Halmai, Ákos; Czigány, Szabolcs (Geographica Pannonica, 2022)
Over the past decades, in the mountainous, hilly and/or urban areas of Hungary several high-intensity storms were followed by severe flash flooding and other hydrologic consequences. The overall aim of this paper was to upgrade the national flash flood susceptibility map of Hungary first published by Czigány et al. (2011). One elementary watershed level (FFSIws) and three settlement level flash flood susceptibility maps (FFSIs) were constructed using 13 environmental factors that influence flash flood generation. FFSI maps were verified by 2,677 documented flash flood events. In total, 5,458 watersheds were delineated. Almost exactly 10% of all delineated watersheds were included into the category of extreme susceptibility. While the number of the mean-based FFSIs demonstrated a normal quasi-Gaussian distribution with very low percentages in the quintile of low and extreme categories, the maximum-based FFSIs overemphasized the proportion of settlements of high and extreme susceptibility. These two categories combined accounted for more than 50% of all settlements. The highest accuracy at 59.02% for class 5 (highest susceptibility) was found for the majority based FFSIs. The current map has been improved compared to the former one in terms of (i) a higher number of conditional factors considered, (ii) higher resolution, (iii) being settlement-based and (iv) a higher number of events used for verification.